Patriotisme dalam Novel Tan Karya Hendri Teja - Muhammad Fadhil Akbar; Nessa Riska Pangesti (Persona: Kajian Bahasa dan Sastra, 2024)
This research aims to describe: (1) the forms of patriotism in Hendri Teja's novel Tan, (2) the causes of patriotism in the novel, and (3) the impact of patriotism within the story. The object of this research is Tan, a novel by Hendri Teja published in 2016. The study employs a descriptive literary research method. The data comprises words, phrases, clauses, and sentences related to patriotism, including the narrator's explanations, character dialogues, and actions within the novel. The primary instrument for this research is the researcher, who utilizes various formats for both data collection and analysis. The data collection techniques involve reading and thoroughly understanding the novel, identifying and categorizing the characters, marking relevant utterances and narrations, and compiling the data in alignment with the research questions. The data analysis technique involves several steps: (1) identifying data related to patriotism in the novel, (2) analyzing the gathered data, and (3) drawing conclusions regarding the issues of patriotism and presenting them in a thesis format. The findings of this study reveal three key aspects: (1) the different forms of patriotism exhibited by the characters, (2) the underlying causes of these patriotic expressions, and (3) the subsequent impact of patriotism on the characters and the narrative. The focus of this research remains on Tan, emphasizing the comprehensive examination of patriotic elements as portrayed by Hendri Teja.